Analysis of space and housing based on the new considerations derived from the COVID-19 pandemic. An approach to housing in Mazatlan, Sin. Mexico - Medina, Elizabeth Adriana Valdez; Pereda, José Francisco Lizárraga; Medina, Filiberto Enrique Valdes; Gonzalez, Sylvia Cristina Rodriguez (Seven Editora, 2023)
This document examines the minimum housing characteristics that must be reconsidered to address emerging needs from the health crisis derived from the COVID-19 virus pandemic. Since the needs of society are constantly evolving, it is important to re-evaluate the minimum requirements for adequate housing. As people’s lifestyles and family structures change, so do their housing expectations. In the present investigation, some of the issues that make the revaluation of the house necessary are enunciated. DOI:https://doi.org/10.56238/emerrelcovid19-058